Editorial: Perspectives on Machine Learning - Haw, Su-Cheng (Journal of Telecommunications and the Digital Economy, 2024)
Progress in machine learning technology has truly impacted our lives by tailoring many of our daily experiences to be seamless and intuitive. This innovation has brought about changes in day-to-day routines; from suggesting music based on our emotions to offering recommendations for places to visit or meals to try out. This special issue explores various Machine Learning technologies. Among some are Machine Learning advances that improve human interaction, predict user behaviours, analyse user reviews, and optimize high-risk investments like Bitcoin trading. These technologies enhance user experiences, help businesses refine marketing strategies, and provide quick insights from vast amounts of information, elevating AI to new heights. With the rise of transformation into advanced technologies taking prominence in our lives, we expect to see these machine learning innovations being integrated across many sectors and uses.